The Threats of Climate Change in Nepal: Natural Catastrophes and Global Conflict Frontiers - Karki, Balkrishna (Unity Journal, 2024)
Nepal, nestled amidst the majestic Himalayas, is uniquely positioned with its delicate geological makeup. This renders it vulnerable to escalating environmental threats, primarily driven by global climate change-induced adversities. These climatic adversities not only disrupt the ecological balance but also create a space for multiple conflict frontiers. The primary objective of this research is to delve into the multifaceted conflicts that include competition for scarce resources, decision-making process, and vested interest of foreign powers that may arise from the climatic challenges especially flash floods, glacier lake outbursts, droughts, landslides, and other catastrophic disasters. The study aims to provide a comprehensive understanding of climatic-induced disaster events and their significant role in the origin of conflicts. Employing a qualitative research design using the tool of comparative analysis, the study investigates the conflicts triggered by these disasters of the past two decades. The study will draw insightful parallels between Nepal's unique situation and other global regions. I will spotlight regions like South Sudan, Rwanda, Syria, and, South and Southeast Asia where climate-induced factors, such as acute water and food shortages, have ignited community tensions and other resource-based conflicts in the historical review and analysis. Within Nepal's borders, I will undertake a detailed historical analysis of the specific cases due to climate change. The study aims to bridge the knowledge gap between climate change and conflict dynamics, offering actionable insights for holistic resource management, disaster risk mitigation, and proactive conflict prevention.